Analysis of Liver Fibrosis Degree with APRI Score and FIB-4 Index on Patients with Non-Alcoholic Fatty Liver Disease - Gillian Elvira Seipalla; Nurahmi Nurahmi; Ibrahim Abd Samad (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2020)
Liver fibrosis is the accumulation of Extracellular Matrix Protein (EMP) scar tissue after acute or chronic liver injury. Liver biopsy is the gold standard test for evaluating liver fibrosis in patients with Non-Alcoholic Fatty Liver Disease (NAFLD). This diagnostic method is invasive, painful, and complicated in rare cases; thus the noninvasive methods such as laboratory tests and radiology had been proposed to assess liver fibrosis in NAFLD and are expected to overcome the limitations of liver biopsy. This method consists of aspartate Aminotransferase to the Platelet Ratio Index (APRI) and fibrosis-4 (FIB-4).Thisresearch was retrospective cross-sectional performed at Dr. Wahidin Sudirohusodo Hospital Makassar involving 63 subjects from January to June 2018. The correlated variables were presented in categorical and numerical data and the Pearson correlation test was used to determine the compatibility of APRI score and FIB-4 index with Fibroscan result in patients with NAFLD. A highly significant positive correlation (p <0.001) was found between APRI score and Fibroscan (correlation value = 45.8%), APRI score and FIB-4 index (correlation value = 91.8%), FIB-4 index and Fibroscan (correlation value = 47.6%). The score of Aminotransferase to platelet ratio index score and FIB-4 index could be an alternative method instead of a liver biopsy to predict the degree of fibrosis in patients with NAFLD.